2019
DOI: 10.1590/s1980-220x2018006103457
|View full text |Cite|
|
Sign up to set email alerts
|

Hypertension is the underlying cause of death assessed at the autopsy of individuals

Abstract: Objective: To analyze hypertension and its relationship with the causes of death identified by the autopsy. Method: Cross-sectional study analyzed 356 participants belonging to the Brazilian Aging Brain Study Group, over 50 years of age, autopsied at the Sao Paulo Autopsy Service between 2004 to 2014. A clinical interview was conducted with the informant of the deceased. Hypertension was defined by reporting the disease and/or use of antihypertensive medication, by the informant of the deceased. Descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(30 reference statements)
0
3
0
7
Order By: Relevance
“…Another significant variable in the present study was sedentary lifestyle, which is related to a higher prevalence of the disease in both sexes, in this case, the trend among women with a sedentary lifestyle was more likely to present SAH compared to men. Like these findings, other studies revealed that more than 50% of hypertensive individuals did not practice physical exercises, but among them, a study showed the prevalence of sedentary lifestyle among women, with a percentage of 57.5% 16 . In addition, this research showed that physical inactivity is the factor that influences survival in hypertension among men, although smoking is more prevalent, as highlighted by a study conducted in Paraná, in which the association avoided and previously dissipated with SAH 17 .…”
Section: International Journal Of Advanced Engineering Research and Science (Ijaers)mentioning
confidence: 52%
“…Another significant variable in the present study was sedentary lifestyle, which is related to a higher prevalence of the disease in both sexes, in this case, the trend among women with a sedentary lifestyle was more likely to present SAH compared to men. Like these findings, other studies revealed that more than 50% of hypertensive individuals did not practice physical exercises, but among them, a study showed the prevalence of sedentary lifestyle among women, with a percentage of 57.5% 16 . In addition, this research showed that physical inactivity is the factor that influences survival in hypertension among men, although smoking is more prevalent, as highlighted by a study conducted in Paraná, in which the association avoided and previously dissipated with SAH 17 .…”
Section: International Journal Of Advanced Engineering Research and Science (Ijaers)mentioning
confidence: 52%
“…Samples of abnormal areas of organs such as the kidney, spleen, lung, liver, heart, and brain are collected for anatomopathologic analysis. A brief report regarding how the death occurred and preexisting diseases is also collected with a close family member to confront macro and microscopic findings 25…”
Section: Methodsmentioning
confidence: 99%
“…A brief report regarding how the death occurred and preexisting diseases is also collected with a close family member to confront macro and microscopic findings. 25 In our analysis, we have considered the CoD reported in the full-body autopsy carried out by a pathologist. As death can be a multifactorial event, all national full-body autopsy reports are filled in according to a hierarchical chain of events that led to a person's death, CoD being the last event.…”
Section: Full-body Autopsy Reportsmentioning
confidence: 99%
“…Таким образом, вероятно, даже проведение патологоанатомических исследований в отсутствие четко прописанных согласованных на международном уровне критериев не улучшает ситуацию с определением первоначальной причины смерти. По данным исследования, выполненного в Бразилии среди 356 умерших старше 50 лет от естественных причин, артериальная гипертензия была второй ведущей первоначальной причиной смерти (25,6%) после атеросклероза (37,8%), но в статье нет критериев установления первоначальной причины смерти от артериальной гипертензии -практически у всех пациентов с этим состоянием наблюдалась коморбидная патология, и не совсем ясно, почему именно артериальная гипертензия была установлена как первоначальная причина смерти [17]. L. Rethy и соавт.…”
Section: оригинальные статьиunclassified